Cladistic and biogeographic analyses of the genera Moscharia and Polyachyrus (Asteraceae, Mutisieae) - Katinas, Liliana (2000)
The genera Moscharia (two species) and Polyachyrus (seven species) form a monophyletic group within tribe Mutisieae, subtribe Nassauviinae, defined by the leaves with auricles at their bases, and the capitula with 1-seriate involucre. A cladistic analysis of the species of the two genera was carried out using 22 characters from life cycle, external morphology, pollen, and trichomes. Polarity of the characters was based on the outgroup comparison method. One cladogram was produced, with 37 steps, a consistency index of 0.73, and a retention index of 0.75. The cladogram defines six monophyletic groups: (((Polyachyrus annus, (P. carduoides, (P. cinereus, (P. fuscus, P gayi))), P sphaerocephalus), P. poeppigii), (Moscharia solbrigii, M. pinnatifida)). The probable ancestral geographic area for the group, determined by Bremer's method, is North- Central Chile area (30°-35°south latitude). The study suggests that the Pleistocene could be the period of evolution of the ancestor of Moscharia and Polyachyrus.